Determinants for hospitalisations, intensive care unit admission and death among 20,293 reported COVID-19 cases in Portugal, March to April 2020 - Peixoto, Vasco Ricoca (2021)
Publisher Copyright: © 2021 European Centre for Disease Prevention and Control (ECDC). All rights reserved.